SISTEM PELAPORAN PERITUNGAN JUMLAH PENUMPANG BUS VIA SMS BERBASIS ARDUINO UNO - , DODDY SURYO PERMADI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This tool is a system designed to make it easier and speed up the recording or logging passengers process on the bus. This system has the ability to be able to record passenger data and also the coordinates of bus locations and sending the data via short messages (SMS). This device consists of four basic device, that is the Arduino Uno which acts as the brain or the main controller, A6390 GSM module is useful for sending data via short messages (SMS), PMB-648 GPS module is useful to provide information such as the coordinates of bus locations, LCD Keypad Shield that is used to display the data as well as a controller. With Passengers Bus Recording System Via Sms Based Arduino Uno, the data summary process will be faster and easier. However, this system still has many weaknesses, which depends on the condition of GSM and GPS signals.